2013
DOI: 10.1186/1746-160x-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of fibroblast density in the human periodontal ligament

Abstract: ObjectiveRecently, research has focused intensely on age-related tissue changes, not only in the field of dermatology but also in dental sciences. Although many new insights into age-related morphological, ultrastructural and biochemical changes in the periodontal ligament tissue have been gained, the basic question of whether there is a quantitative change in cell number remains unanswered or, at least to date, unpublished. Thus, the aim of this study was to detect age-related changes of the periodontal ligam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…The clinical literature is replete with examples of how tissues adapt to physical forces. In the craniomaxillofacial skeleton, tooth loss predictably leads to alveolar bone atrophy (Canger and Celenk 2012) and a thinning of the periodontal ligament (PDL; Denes et al 2013;Krieger et al 2013). Conversely, hyperloading of the dentition causes a thickening of the PDL (Mortazavi and Baharvand 2016) and alveolar bone accrual (Carlsson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical literature is replete with examples of how tissues adapt to physical forces. In the craniomaxillofacial skeleton, tooth loss predictably leads to alveolar bone atrophy (Canger and Celenk 2012) and a thinning of the periodontal ligament (PDL; Denes et al 2013;Krieger et al 2013). Conversely, hyperloading of the dentition causes a thickening of the PDL (Mortazavi and Baharvand 2016) and alveolar bone accrual (Carlsson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…, Van der Velden , Krieger et al. ). In this study we found no differences in cell density over the mice's lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge on the effects of ageing on the periodontium is largely based on in vitro studies that evaluate primary cell cultures from donors of different ages, or compare cells from lower versus higher passage numbers or young versus old cell culture media (Krieger et al. ). These analyses do not clearly indicate how chronological age affects the remodelling and repair of the periodontium in a living animal.…”
mentioning
confidence: 99%
“…With an increasingly aging population, a better understanding of the age-related changes in resident stem cell function and microenvironment is critical in developing and optimizing rejuvenation strategies to reverse the aging process for effective therapeutic treatment (Gibon et al, 2016). Aged teeth are characterized by a decrease in the regeneration of dental pulp (Iohara et al, 2014), stenosis and fibrosis of the periodontal ligament (Krieger et al, 2013), widening of the cementum, and constriction of the apical region (Jang et al, 2014), affecting resident stem cell function and the homeostasis of the tooth and associated tissue. Resident cells in the tissue surrounding the aged tooth have lower potential of migration, proliferation, and cell survival (Iohara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%